2002
DOI: 10.1002/app.2266.abs
|View full text |Cite
|
Sign up to set email alerts
|

Miscibility and adhesive properties of ethylene vinyl acetate copolymer (EVA)-based hot-melt adhesives. I. Adhesive tensile strength

Abstract: A series of ethylene vinyl acetate copolymers (EVA) were blended with some tackifier resins that are made from wood extracts, and possible relations between their miscibility and properties as hot-melt adhesives (HMA) were investigated. From our previous report on miscibility of various EVA-based HMAs, we chose some blends that represent some of typical miscibility types and measured their adhesive tensile strengths. When the blends were miscible at testing temperatures, the temperature at which the maximum va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 3 publications
1
20
0
Order By: Relevance
“…The lack of effect of the molecular weight on the isomerization rate remained unclear, but the authors suggest that it may be related to the relatively high molecular weights employed in this study. In single‐lap shear experiments using glass substrates, maximum adhesive strength around 3.5 MPa was obtained, which is comparable to the adhesive strength of typical hot‐melt adhesives . The bond strength rapidly decreased to <0.2 MPa upon UV irradiation (λ = 365 nm, 50 mW cm −2 , 15 s), which demonstrates that the above polymers can be used as reversible on‐demand debondable adhesives.…”
Section: On‐demand Debonding Based On Reversible Bondssupporting
confidence: 54%
“…The lack of effect of the molecular weight on the isomerization rate remained unclear, but the authors suggest that it may be related to the relatively high molecular weights employed in this study. In single‐lap shear experiments using glass substrates, maximum adhesive strength around 3.5 MPa was obtained, which is comparable to the adhesive strength of typical hot‐melt adhesives . The bond strength rapidly decreased to <0.2 MPa upon UV irradiation (λ = 365 nm, 50 mW cm −2 , 15 s), which demonstrates that the above polymers can be used as reversible on‐demand debondable adhesives.…”
Section: On‐demand Debonding Based On Reversible Bondssupporting
confidence: 54%
“…After a TPA bond has been formed, its bonding strength can be dramatically influenced by the temperature of the bond [47], [51], [52]. As the temperature increases from room temperature, bonding strength first exponentially decreases, and separation results from interfacial adhesive failure between TPAs and adherends.…”
Section: B Temperature Dependence Of Bonding Strengthmentioning
confidence: 99%
“…Moreover, it has been reported that bonding strength could still be maintained under the presence of alien material, e.g., water [49] or clay minerals [50], showing that HMAs are robust toward external disturbance. Upon cooling to room temperature, HMAs will be hardened and the bonding strength can be as high as 1-10 MPa [47], [51], [52].…”
Section: A Adhesion Through Thermal Bondingmentioning
confidence: 99%
“…The tackifier improves the mobility of the base polymer during the taping process by acting as a diluent and also improves the peel strength during the peeling process. Many researchers1–8 have investigated the mechanism of tack improvement through the addition of tackifiers.…”
Section: Introductionmentioning
confidence: 99%